Efektivitas Penegakan Hukum oleh Penyidik Pegawai Negeri Sipil Kehutanan terhadap Perdagangan Satwa Liar yang Dilindungi: (Studi Kasus Pada Seksi Wilayah I Balai Pengamanan dan Penegakan Hukum Lingkungan Hidup dan Kehutanan Wilayah Sumatera) - Hadyan Hindami; Nelvitia Purba (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rise of trade in protected wildlife threatens the preservation of biodiversity in Indonesia, especially in the Aceh and North Sumatra regions. This is because punishment does not provide a deterrent effect to the perpetrators and the involvement of officials in its implementation, so that law enforcement against the trade in protected wildlife has not been felt effective in the eyes of the public. In this thesis, the author wants to know the extent of the effectiveness of law enforcement carried out by Forestry Civil Servant Investigators (PPNS) against protected wildlife trade through issues related to law enforcement, obstacles in law enforcement and efforts that have been made to overcome these obstacles. This research was conducted in Section I of the Sumatra Regional Environmental and Forestry Law Enforcement Center. The research method used is a case study with a qualitative approach. Data was collected through interviews with PPNS Forestry and related parties, as well as analysis of documents related to protected wildlife trafficking cases. The results of the study show that the effectiveness of law enforcement by PPNS Forestry has been quite effective, although it is still faced with several obstacles in its implementation. Law enforcement against the trade in protected wildlife starts from preemptive, preventive, repressive and judicial actions. Light punishment, the use of undercover buy techniques, proof of evidence, involvement of officials, facilities and infrastructure, human resources and public awareness are still factors that hinder law enforcement. Therefore, efforts have been made to overcome these obstacles by revising the law, strengthening intelligence networks, adding and increasing human resources, coordinating with related agencies and socializing to the community. The author recommends that socialization be carried out to law enforcement officials regarding the equality of perception in the implementation of Law Number 32 of 2024 and establish close cooperation with the TNI and Polri intelligence networks and make strict rules against officers involved in the trade of protected wildlife.